2023
DOI: 10.3390/vaccines11010196
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Knowledge, Attitudes and Behaviours of Health Care Workers towards Vaccine-Preventable Diseases and Recommended Vaccinations: An Observational Study in a Teaching Hospital

Abstract: Background: Recommended vaccinations are the cheapest and most effective measure to reduce the risk of transmission and related complications, especially in high-risk healthcare settings. This study aimed to evaluate the knowledge, attitudes and behaviours of HCWs in relation to national recommendations. Methods: A transversal study was conducted through administration of a questionnaire by personal interview. The following care units were involved: Paediatric, Neonatal, Cardiac Surgery and General Intensive C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Even the Spanish GPs had slight scepticism when it comes to safety and efficacy of elderly vaccination schedules [25] . Riccio et al, found an overall inadequate perception regarding the dangerousness and risk of some VPDs with 20% believing that the risks of vaccination outweigh the benefits [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Even the Spanish GPs had slight scepticism when it comes to safety and efficacy of elderly vaccination schedules [25] . Riccio et al, found an overall inadequate perception regarding the dangerousness and risk of some VPDs with 20% believing that the risks of vaccination outweigh the benefits [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the pharmacist must be attentive to the patient’s history and/or pathologies and/or allergies and/or chronic treatments to minimize any risk of possible drug interaction or contra-indication. The pharmacist must also be continuously trained on the different measures of protection, ongoing developments [ 43 ], such as the use and characteristics of the malaria vaccine RTS,S/AS01 [ 1 , 44 ] or the new types of insecticide-treated nets (pyrethroid and piperonyl butoxide treated nets) [ 1 , 23 , 45 ], even if these tools do not concern travelers and are therefore not available in Europe to date.…”
Section: Role In the Prevention Of Malaria Infectionsmentioning
confidence: 99%
“…The literature primarily concentrates on parents, revealing that those with good knowledge and positive attitudes towards vaccinations are more likely to vaccinate their children, especially those with higher levels of education [33][34][35]. Additionally, other studies have been conducted among healthcare providers, indicating that physicians and younger individuals generally possess more knowledge and a better understanding of vaccination recommendations compared to other healthcare workers [36][37][38][39]. However, it is important to note that, due to the impact of the pandemic on academia, most of the recent studies focus specifically on hesitancy related to COVID-19 vaccination, neglecting the importance of other vaccinations [40].…”
Section: Introductionmentioning
confidence: 99%